Review of Manganese Processing for Production of TRIP/TWIP Steels, Part 1: Current Practice and Processing Fundamentals - Elliott, R.; Coley, K.; Mostaghel, S.; Barati, M. (JOM (1989), 2018)
The increasing demand for high-performance steel alloys has led to development of transformation-induced plasticity (TRIP) and twinning-induced plasticity (TWIP) alloys over the past three decades. These alloys offer exceptional combinations of high tensile strength and ductility. Thus, the mechanical behavior of these alloys has been a subject of significant work in recent years. However, the challenge of economically providing Mn in the quantity and purity required by these alloys has received considerably less attention. To enable commercial implementation of ultrahigh-Mn alloys, it is desirable to lower the high material costs associated with their production. Therefore, the present work reviews Mn processing routes in the context of the chemical requirements of these alloys. The aim of this review is to assess the current state of the art regarding reduction of manganese ores and provide a comprehensive reference for researchers working to mitigate material processing costs associated with Mn production. The review is presented in two parts: Part 1 introduces TRIP and TWIP alloys, current industrial practice, and pertinent thermodynamic fundamentals; Part 2 addresses available literature regarding reduction of Mn ores and oxides, and seeks to identify opportunities for future process development.